2022
DOI: 10.3390/math10214127
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Meta-Heuristic Algorithms for Integrated Batch Manufacturing and Delivery Scheduling Problem

Abstract: This paper addresses an integrated scheduling problem of batch manufacturing and delivery processes with a single batch machine and direct-shipping trucks. In the manufacturing process, some jobs in the same family are simultaneously processed as a production batch in a single machine. The batch production time depends only on the family type assigned to the production batch and it is dynamically adjusted by batch deterioration and rate-modifying activities. Each job after the batch manufacturing is reassigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Other recently related studies can be found in Zhang et al [12], Masadeh et al [13], Zhang et al [14], Kim and Kim [15], Valouxis et al [16], and Wang et al [17] among many others.…”
Section: Notation Terminology P Jmentioning
confidence: 91%
“…Other recently related studies can be found in Zhang et al [12], Masadeh et al [13], Zhang et al [14], Kim and Kim [15], Valouxis et al [16], and Wang et al [17] among many others.…”
Section: Notation Terminology P Jmentioning
confidence: 91%
“…In studies regarding electric vehicle (EV) systems, metaheuristics have been implemented to optimize the routing problem of the plugin hybrid electric vehicles (PHEV) [1], fast charging stations [2], distributed photovoltaic systems [3], and so on. In studies regarding manufacturing systems, metaheuristics have been implemented to optimize the coupling between integrated batch machines and direct shipping trucks [4], reducing risk in the spare part inventory system [5], and so on. In studies regarding power systems, metaheuristics have been implemented to optimize the installation and allocation of the distributed generation units [6], radial distribution system [7], reactive power flow in the large-scale power system [8], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of computer technology and the change in social demand, product scheduling in the manufacturing industry is transformed from single machine scheduling to distributed scheduling [3,4]. In the era of big data and artificial intelligence, product scheduling methods based on cloud computing and fog computing are also developing rapidly [5,6].…”
Section: Introductionmentioning
confidence: 99%